THE IMPLEMENTATION OF FORMATIVE AND SUMMATIVE EVALUATION SYSTEMS IN ENHANCING STUDENT LEARNING OBJECTIVES - Febriyani, Fifi Nur Lynda; Anshori, Ari; Maulaya, Rosendah Dwi (Proceeding of International Conference of Islamic Education, 2024)
Evaluation is a crucial component in the educational process, serving to measure and assess student learning achievements. Evaluation is not merely an assessment tool but also an integral part of a continuous learning process. The formative evaluation system, which focuses on ongoing monitoring and feedback during the learning process, and the summative evaluation system, which assesses student understanding at the end of the learning period, are analyzed to determine their contributions to student learning outcomes. This research aims to examine the effectiveness of formative and summative evaluation systems in enhancing student learning objectives at SMP Nurul Mustofa, Klaten. The research method used is qualitative, with a descriptive approach and field analysis. Data were collected through interviews and several articles related to evaluation systems. The research findings indicate that formative evaluation significantly helps students understand learning material more deeply through continuous feedback. Meanwhile, summative evaluation provides a comprehensive overview of student achievements and is effective in assessing the final learning outcomes. The combination of these two evaluation systems has proven to increase student motivation and the overall achievement of learning objectives. These findings suggest that a balanced implementation of formative and summative evaluations can optimize the learning process and academic achievement of students at SMP Nurul Mustofa, Klaten.